2020
DOI: 10.1002/app.50132
|View full text |Cite
|
Sign up to set email alerts
|

3D printing‐assistedcombinatorial approach for designing mechanically‐tunable and vascular supportive nanofibrous membranes to repair perforated eardrum

Abstract: Perforation of eardrum or tympanic membrane (TM) is a common clinical condition, which occurs due to infection or injury of the eardrum, and could results in varying degrees of conductive hearing loss among all ages. In this study, the authors report the combinatorial approach of designing mechanically-tunable and vascular supportive nanofibrous membranes by 3D printing-assisted electrospinning (e-spin) using polycaprolactone (PCL) and gelatin with different mass ratios suitable to repair a perforated eardrum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Cell proliferation activity was quantified using the Cell Counting Kit‐8 (CCK‐8, Servicebio) as previously reported approach. [ 51 ] Briefly, the sterilized scaffolds were treated with culture medium for 48 h to prepare the leaching solution in advance. The cell suspension was prepared by the treated culture medium with a density of 1 × 10 5 cells mL −1 and then 100 µL cell suspension was seeded in 96‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Cell proliferation activity was quantified using the Cell Counting Kit‐8 (CCK‐8, Servicebio) as previously reported approach. [ 51 ] Briefly, the sterilized scaffolds were treated with culture medium for 48 h to prepare the leaching solution in advance. The cell suspension was prepared by the treated culture medium with a density of 1 × 10 5 cells mL −1 and then 100 µL cell suspension was seeded in 96‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…119 Nevertheless, significant progress has already been made in this area recently. 60,61,[122][123][124] Lee et al demonstrated, as a proof of concept, the application of a human recombinant elastic bio-ink with which they could bioprint a vascularized cardiac construct that displayed the endothelium barrier function. 125 Therefore, constructing complex hierarchical vascularized networks in bioprinted tissue construct and establishing a connection with the host by surgical anastomosis or other technical solutions are issues that need to be addressed urgently.…”
Section: Clinical Translation Of Bioprinted Productsmentioning
confidence: 99%
“…[17][18][19] Recent studies have shown that PCL can prompt vascular growth and wound healing with its good mechanical properties and slow degradation kinetics. [20][21][22] For the fabrication of patches, various mothed and manufacture processes were developed in the past decade years, one of commonly methods is knitting, which is to form the desired patch by bending the filaments into circles and then serially sheathing each other. However, knitted patch not only requires special equipment, but also has poor flexibility in design and material, so it is difficult to realize personalized customization for different patients.…”
Section: Introductionmentioning
confidence: 99%